Production structure, tradability and fiscal spending multipliers - Jesús Crespo Cuaresma; Christian Glocker (Austrian Institute of Economic Research (WIFO), 2023)
We assess the role that nontradable goods play as a determinant of fiscal spending multipliers, making use of a two-sector model. While fiscal multipliers increase with the share of nontradable goods, an inverted U-shaped relationship exists between multiplier size and the import share. Employing an interacted panel VAR model for EU countries, we estimate the effect of the share of nontradable goods on fiscal spending multipliers. Our empirical results provide strong evidence for the predictions of the theoretical model. They imply that the drag of fiscal consolidations is on average smaller in countries with a low share of nontradable goods.
Keywords: E23; E62; F41; C23; 330; Fiscal spending multiplier; Nontradable goods; Openness; DSGE model; Interacted panel VAR model